(untitled) (ENTHYMEMA, 2022)
This essay offers a reading of Mariangela Gualtieri’s play Caino. The first part of our study looks at similarities and differences between Gualtieri’s rewriting and the biblical myth, traces likely source texts for the work and examines it using the tools of psychoanalysis, focusing in particular on the theme of envy, of the different images of God and of the consequences related to scientific and technological progress. The second part is devoted to a comparison between Gualtieri’s Cain and the characters of the same name we find in Saramago’s and Camilleri’s books.